Analisis Dogmatik terhadap Legalitas Hak Guna Bangunan di atas Tanah Wakaf: Perspektif Hukum Perjanjian Indonesia - Friqly Aldinda Ganadi; Moh Mahrus; Lilik Andaryuni (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to examine the legality of granting HGB over waqf land through a dogmatic legal analysis from the perspective of Indonesian contract law. The research employs a qualitative normative legal method based on library research, analyzing primary legal materials, including the Basic Agrarian Law, the Waqf Law, Government Regulation No. 18 of 2021, and the Indonesian Civil Code, supported by relevant secondary legal sources. The findings demonstrate that the legality of HGB over waqf land can only be justified where the underlying agreement satisfies the requirements for a valid contract, particularly the clarity of contractual subjects and objects, a lawful causa aligned with the purposes of waqf, and the application of the principles of good faith and balance of interests. These findings underscore the urgent need for regulatory reconstruction to ensure that productive waqf development operates within a framework of legal certainty while preserving the social and religious values of waqf.